Assessment of flavanol stereoisomers and caffeine and theobromine content in commercial chocolates. (1st October 2016) - Alañón, M.E.; Castle, S.M.; Siswanto, P.J.; Cifuentes-Gómez, T.; Spencer, J.P.E.
Highlights: Epicatechin concentration could predict the total flavanols and procyanidin content. No correlation was found between catechin content and the rest of flavanols. % Cocoa solids is no clear indicator of (−)-epicatechin, the most bioactive compound. Abstract: Assessment of the flavanol composition of 41 commercial chocolates was by HPLC-DAD. Among individual flavonols ranged from 0.095 to 3.264 mg g −1, epicatechin was the predominant flavanol accounting for 32.9%. Contrary to catechin, epicatechin was a reliable predictive value of the polyphenol content. Conversely the percentage of theobromine used as a proxy measure for nonfat cocoa solids (NFCS) was not a good predictor of epicatechin or flavanol content. In a further chiral analysis, the naturally occurring forms of cocoa flavanols, (−)-epicatechin and (+)-catechin, was determined joint the occurrence of (+)-epicatechin and (−)-catechin due to the epimerization reactions produced in chocolate manufacture. (−)-Epicatechin, the most bioactive compound and predominant form accounted of 93%. However, no positive correlation was found with% cocoa solids, the most significant quality parameter.